2016
DOI: 10.1002/chem.201604237
|View full text |Cite
|
Sign up to set email alerts
|

Photocontrol of Polar Aromatic Interactions by a Bis‐Hemithioindigo Based Helical Receptor

Abstract: The first example of a bis-hemithioindigo (bis-HTI)-based molecular receptor was realized. Its folding and selective binding affinity for aromatic guest molecules can be precisely controlled by visible light and heat. The thermodynamically stable state of the bis-HTI is the s-shaped planar Z,Z-configuration. After irradiation with 420 nm light only the E,Z-configuration is formed in a highly selective photoisomerization. The E,Z-isomer adopts a helical conformation because of the implementation of repulsive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 78 publications
0
29
0
Order By: Relevance
“…More recent applications include digital information processing with a pH‐sensitive HTI molecule; a visible‐light‐responsive supramolecular receptor (HTI tweezers), the folding and affinity for aromatic guest molecules of which can be altered by irradiation and heating, or even light‐driven relocation of the guest between two such receptors …”
Section: Photoresponsive Materials and Nanostructuresmentioning
confidence: 99%
“…More recent applications include digital information processing with a pH‐sensitive HTI molecule; a visible‐light‐responsive supramolecular receptor (HTI tweezers), the folding and affinity for aromatic guest molecules of which can be altered by irradiation and heating, or even light‐driven relocation of the guest between two such receptors …”
Section: Photoresponsive Materials and Nanostructuresmentioning
confidence: 99%
“…[5][6][7] Them ost convenient energy source is arguably light irradiation, which has led to the fastest motions realized so far. [5g] With this hemithioindigo [9] (HTI)-based molecular motor, we achieved very fast rotations (up to 1kHz at 20 8 8C);h owever, this also made full experimental access to the complete directional motion difficult. [5g] With this hemithioindigo [9] (HTI)-based molecular motor, we achieved very fast rotations (up to 1kHz at 20 8 8C);h owever, this also made full experimental access to the complete directional motion difficult.…”
mentioning
confidence: 99%
“…In the research field of photoresponsive materials, indigoid chromophores, gained more and more importance in the last years due to their outstanding redshifted absorption. Hemithioindigo based peptide‐switches, protein inhibitors or molecular devices such as molecular calculators, motors, and receptors are interesting examples for shifting addressability at the molecular scale into the region of less energetic light. Very recently it was reported that di‐arylated indigos can be efficiently photoisomerized while possessing high barriers for thermal cis to trans isomerization .…”
Section: Introductionmentioning
confidence: 99%